Inflammation and its consequences after surgical versus transcatheter aortic valve replacement - Uhle, Florian; Lichtenstern, Christoph; Weigand, Markus A. (Artificial organs, 2018)
Symptomatic aortic stenosis can be treated by surgical aortic valve replacement (SAVR) or transcatheter aortic valve replacement (TAVR), the latter of which is regarded as a minimally invasive procedure. Differences between these procedures regarding immune responses or changes in coagulation and neurocognitive function have thus far been evaluated only sparsely. We carried out a prospective, single-center, nonrandomized explorative study with 38 patients. Thirteen patients were subjected to either SAVR or transfemoral (TF-) TAVR, and 12 patients underwent transapical (TA-) TAVR. Plasma cytokines (IL-6, −8, −18, presepsin) and acute-phase proteins (C-reactive protein, procalcitonin), markers of coagulation and platelet function, and neurocognitive function (via various standard tests) were assessed before and at five-time points during a 72-h follow-up after surgery. SAVR and TA-TAVR patients responded similarly to the procedure in terms of C-reactive protein, leukocyte numbers, and IL-6, whereas these responses were substantially lower in TF-TAVR patients. Only SAVR patients showed measurable IL-10 levels. SAVR patients without prior anticoagulation experienced a robust and transient restoration of platelet function after surgery, with no hypercoagulation observable in functional coagulation assays. None of the procedures led to an immediate improvement of hand and leg coordination, but patients after TA-TAVR had decreased neurocognitive function. Patients after SAVR or TA-TAVR exhibit a robust pro-inflammatory response, which is—on the cytokine level—counterbalanced only in SAVR patients. Our results point toward a greater impact of TA-TAVR on neurocognitive function and indicate a potentially detrimental activation of platelets in some patients after SAVR.